PEMANFAATAN BAHAN ALAM GUNA PEMBUATAN SPOT FOTO DAN BERISTIRAHAT DI DESA SIGAPITON KECAMATAN AJIBATA - Wendy Sudito Pakpahan; Welmar Olfan Basten Barat (Abdi Jurnal Publikasi, 2025)
Sigapiton Village, located in the Ajibata District of Toba Regency, North Sumatra, is situated on the shores of Lake Toba and covers an area of 70.80 km² (BPS, 2018). The village possesses various potentials that can be developed from both human and natural resources. The objective of the KPPM UHKBPNP group's work program in Sigapiton is to create resting areas for the residents, allowing them to take a moment to rest while engaging in their activities.